2011
DOI: 10.1002/hep.24542
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral protein viperin inhibits hepatitis C virus replication via interaction with nonstructural protein 5A

Abstract: The interferon-stimulated gene viperin has been shown to have antiviral activity against hepatitis C virus (HCV) in the context of the HCV replicon, although the molecular mechanisms responsible are not well understood. Here we demonstrate that viperin plays an integral part in the ability of interferon to limit replication of cell culture derived HCV (JFH-1) that accurately reflects the complete viral life cycle. Using confocal microscopy and Fluorescence Resonance Energy Transfer (FRET) analysis we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
261
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(269 citation statements)
references
References 36 publications
8
261
0
Order By: Relevance
“…to prevent viral assembly and/or budding [15,17]. Consistently, removal of N-terminal amphipathic helix domain of human viperin results in a homogenous cytoplasmic distribution when transfection of Huh-7 cells, which coincides with a loss of its ability to inhibit HCV replication [17].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…to prevent viral assembly and/or budding [15,17]. Consistently, removal of N-terminal amphipathic helix domain of human viperin results in a homogenous cytoplasmic distribution when transfection of Huh-7 cells, which coincides with a loss of its ability to inhibit HCV replication [17].…”
Section: Introductionmentioning
confidence: 71%
“…Consistently, removal of N-terminal amphipathic helix domain of human viperin results in a homogenous cytoplasmic distribution when transfection of Huh-7 cells, which coincides with a loss of its ability to inhibit HCV replication [17]. In another paper, sequential deletion of the N-terminal region disrupts ER-association of human viperin in the transfected HEK-293T cells, resulting in its progressive accumulation in cytosol [16].…”
Section: Introductionmentioning
confidence: 74%
“…The consensus from these studies is that viperin likely exerts its activity through different pathways that depend on the particular virus and that it interacts with multiple cellular and viral proteins in the process (19,27,31,33,34). Previous studies, using a truncated version of viperin, recombinantly produced and purified from E. coli, have demonstrated that the enzyme cleaves SAM to form 5Ј-dA (22), which is the hallmark reaction of radical SAM enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, viperin was characterized as one of IFN-inducible antiviral effectors (Carlton-Smith and Elliott, 2012;Fitzgerald, 2011;Helbig et al, 2011;Jiang et al, 2008;Mattijssen and Pruijn, 2012;Overby et al, 2009;Quraishi et al, 2010), and its expression regulation has been investigated in mammals (Boudinot et al, 2000;Chan et al, 2008;Chin and Cresswell, 2001;Olofsson et al, 2005;Saitoh et al, 2011;Severa et al, 2006;Stirnweiss et al, 2010). However, this information in fish is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Viperin is capable to inhibit the release of influenza virus by perturbing lipid rafts (Wang et al, 2007) or to limit the replication of hepatitis C virus by interacting with nonstructural protein 5A (Helbig et al, 2011). Overexpression of viperin promotes TLR7-and TLR9-mediated production of type I IFN in mouse plasmacytoid dendritic cells (Saitoh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%